A Conceptual Review of Lab-Based Aggression Paradigms - Randy J. McCarthy; Malte Elson (Collabra: Psychology, 2018)
Aggression is often defined as a behavior that is done with the intent to harm an individual who is believed to want avoid being harmed (e.g., Baron & Richardson, 1994). Accordingly, social scientists have developed several tasks to study aggression in laboratory settings; tasks that we refer to as “lab-based aggression paradigms.” However, because of the legal, ethical, and practical issues inherent in provoking aggression within the confines of a laboratory setting, it is feasible to study only very mildly harmful aggression. The current conceptual review examines the criteria that are necessary to study aggression in a laboratory setting, discusses the strengths and weaknesses of several new and/or commonly-used lab-based aggression paradigms, and offers recommendations for the future of lab-based aggression research. Collectively, we hope the current discussion helps researchers to describe the contributions and limitations of lab-based aggression research and, ultimately, helps to improve the informativeness of lab-based aggression research.